2011
DOI: 10.1177/0163278711399572
|View full text |Cite
|
Sign up to set email alerts
|

Surveying Nurses

Abstract: While surveys of nurses are an important tool in health services and policy research, they are often characterized by low response rates. The authors conducted a systematic review of 22 published reports of efforts to improve response rates to nurse surveys. Two general strategies were explored in this literature: incentive and design-based approaches. Even small financial incentives were found to be effective in improving nurse survey participation. Token nonmonetary incentives, in contrast, were much less ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(35 citation statements)
references
References 72 publications
0
32
0
Order By: Relevance
“…Our results contribute to the growing body of research about methods to increase response rates and reduce nonresponse bias in provider surveys (Field et al, 2002; Klabunde et al, 2012; VanGeest et al, 2007), with specific consideration to the importance of determining the procedures and incentives for encouraging response among healthcare professionals other than physicians (Camunas et al, 1990; Gore-Felton, Koopman, Bridges, Thoresen, & Spiegel, 2002; Kramer, Schmalenberg, & Keller-Unger, 2009; Ulrich et al, 2005; VanGeest & Johnson, 2011). Our experiences demonstrate that it is possible to obtain a high-quality representative sample of two providers in a long-term care facility.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Our results contribute to the growing body of research about methods to increase response rates and reduce nonresponse bias in provider surveys (Field et al, 2002; Klabunde et al, 2012; VanGeest et al, 2007), with specific consideration to the importance of determining the procedures and incentives for encouraging response among healthcare professionals other than physicians (Camunas et al, 1990; Gore-Felton, Koopman, Bridges, Thoresen, & Spiegel, 2002; Kramer, Schmalenberg, & Keller-Unger, 2009; Ulrich et al, 2005; VanGeest & Johnson, 2011). Our experiences demonstrate that it is possible to obtain a high-quality representative sample of two providers in a long-term care facility.…”
Section: Discussionmentioning
confidence: 70%
“…For example, a review by VanGeest and colleagues (VanGeest et al, 2007) concluded that modest incentives are associated with improved physician response. Although the number of studies about nurses has been more limited, those that are available have shown any monetary incentive significantly improves response rates over no monetary incentive (Camunas, Alward, & Vecchione, 1990; Odon & Price, 1999; Ulrich et al, 2005; Ulrich & Grady, 2004; VanGeest & Johnson, 2011). However, Flanigan and colleagues (Flanigan, McFarlane, & Cook, 2008) have cautioned that too large of an incentive may be seen as a payment, thereby turning away many health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Although the nurses’ survey was completed on the telephone and ours was via personal contact, they both used personal contact, which can be expensive and may not be as fruitful in other populations. In their review of surveys of nurses, VanGeest and Johnson (2011) found that nurses responded to telephone strategies comparable to those of mail. This differs markedly from studies conducted among physicians, which find poor response to telephone strategies (Cho et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of factors affecting response rates among nonphysician health-care providers have been few, compared to those among physicians, and most were primarily done by mail (Guise, Chambers, Valimaki, & Makkonen, 2010; Hawley, Cook, & Jensen-Doss, 2009; Hill, Fahrney, Wheeless, & Carson, 2006; Paul, Walsh, & Tzelepis, 2005; Ulrich et al, 2005; VanGeest & Johnson, 2011). In general, findings among nonphysician providers are consistent with those among physicians, namely, that monetary incentives, even small amounts, increase response rates compared to no incentives, nonmonetary, or a lottery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation